Incidence of Fetal Myocardial Hypertrophy in Mother with Diabetes Mellitus by Using Cardio-Spatiotemporal Image Correlation (STIC) M-Mode - Sapanont K; Luangdansakul W; Pleankong M; Smanchat B; Bhamarapravatana K; Suwannarurk K (Dove Medical Press, 2023)
Kobporn Sapanont,1 Wiyada Luangdansakul,1 Monyada Pleankong,1 Buppa Smanchat,1 Kornkarn Bhamarapravatana,2 Komsun Suwannarurk3 1Department of Obstetrics and Gynecology, Bhumibol Adulyadej Hospital, Royal Thai Air Force, Bangkok, Thailand; 2Department of Preclinical Sciences, Faculty of Medicine, Thammasat University, Pathum Thani, Thailand; 3Department of Obstetrics and Gynecology, Faculty of Medicine, Thammasat University, Pathum Thani, ThailandCorrespondence: Wiyada Luangdansakul, Department of Obstetrics and Gynecology, Bhumibol Adulyadej Hospital, Royal Thai Air Force, Bangkok, 10220, Thailand, Tel +66-2-5347314, Email nui.obgyn@gmail.comObjective: The aim was to demonstrate the prevalence of fetal myocardial hypertrophy (FMH) in diabetes mellitus (DM) pregnant women using spatio-temporal image correlation (STIC) M-mode.Material and Methods: This prospective descriptive study was conducted at Bhumibol Adulyadej Hospital (BAH) Royal Thai Air Force between April and December 2022. Participants were singleton DM pregnant women with gestational age (GA) between 18 and 40 weeks who had antenatal care and delivery at BAH. DM screening was randomized blood sugar obtained from all participants. All participants underwent fetal heart exams by four-dimension ultrasound with STIC M-mode.Results: One hundred and forty-five participants were recruited and classified as pregestational (PDM) and gestational DM (GDM) at 31 and 114 cases, respectively. The mean age of participants was 31.7 years old. Fasting blood sugar (FBS) of PDM was significantly higher than GDM (105.1 vs 87.0 mg%). GDMA2 had more elevated FBS than GDMA1 (p < 0.001). PDM had significantly greater FBS and two-hour postprandial blood sugar (2hr-PP) than GDM (105.1/87.0 and 151.5/117.9 mg%, respectively). FBS and 2hr-PP of GDMA2 were more than GDMA1 with statistical significance. Good glycemic control of GDM was significantly better than PDM. GDMA1 had better glycemic control than GDMA2 with statistical significance. Four-fifth (115/145) of participants had FMH. FMH and estimated fetal weight among PDM and GDM were comparable. Both good and poor glycemic control had similar FMH. Neonatal outcomes of FMH or non-FMH infants were similar.Conclusion: The prevalence of FMH in diabetic pregnant women was 79.3%. Glycemic control had no correlation to FMH.Keywords: STIC-M, gestational diabetes mellitus, pregestational diabetes mellitus, interventricular septal thickness